EVALUASI RENCANA KINERJA KOLAM RETENSI (RETARDING BASIN) DALAM UPAYA PENGENDALIAN BANJIR TUKAD MATI DI KOTA DENPASAR - Suryadinata P, I G.; Norken, I N.; Sila Dharma, I G. B. (JURNAL SPEKTRAN; Vol 1, No 1, Januari 2013DO - 10.24843/SPEKTRAN.2013.v01.i01.p03, 2013)
Tukad Mati is one of the rivers in the province of Bali that unfolds and flows in Badung regency and Denpasar. Inundation due to flooding is a problem that often occurs in this region during the rainy season. In an effort to overcome problems of flooding have been many studies carried out so as to produce flood control alternatives such as normalization, diversion channels and retarding basins. Retarding basin is one of flood control alternative that has not been much studied. In this study conducted a simulation of flood prevention alternative with retarding basin at Tukad Mati, by the hydrology approach method and hydraulics using HEC-RAS 4.0 program applications. Simulations performed on the current river flow conditions (existing condition) and to the existing conditions with the retarding basin, according to the detail design of retarding basin in the city of Denpasar and evaluate the effectiveness of the retarding basin in the river basin flood control of Tukad Mati. Flood control by retarding basin based on simulations with the 2 (two) years flood return period, resulting in a reduction of water level by an average of 0.42 meters or an average of 12% of the maximum water level in the conditions without retarding basin, which occurred in along the grooves on the lower reaches of the retarding basin and inundation waters still occur in some places, particularly in the downstream of Umadui Dam. Economic analysis of both the analysis of Benefits/Cost produces a parameter of BCR, NPV and IRR are not meet the feasibility requirements. The effective retention of retarding basin based on simulation results are 282,630.00 m 3 with the ability to flood accommodate for 3-4 hours. In terms of economic development retarding basin is not feasible in terms of comparative costs and benefits
Keywords: retention, effectiveness, feasibility.